APPLICATION OF THE INQUIRY LEARNING MODEL IN IMPROVING STUDENT LEARNING OUTCOMES IN CITIZENSHIP EDUCATION (PKN) SUBJECTS IN ELEMENTARY SCHOOL: (Qualitative Descriptive Study Through Library Research) - Okpatrioka Okpatrioka (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
This study aims to improve student learning outcomes by applying the inquiry learning model during teaching and learning activities in Civics Education (PKn) SD . This research is motivated by the low learning outcomes of students in elementary schools because there are still many teachers who do not apply innovative learning models, teacher-centered conventional learning models that make students less active in the learning process. The Inquiry Learning learning model emphasizes the process of critical and analytical thinking to seek and find answers to the problems in question. This research method is the study of literature (Library Research) or library research. The research is motivated by the low student scores, presumably because the learning model is less attractive. Inquiry Learning learning model, namely: (1) orientation; (2) formulate the problem; (3) formulate hypotheses; (4) collect data; (5) testing the hypothesis; (6) formulate conclusion